Automated Criteria Based Group Formation to Improve Team Performance - Mohan, Divya Gopal (IRC, 2020)
Group work has been extensively applied in universities for effective knowledge transfer. Currently, the groups are formed by random grouping, selfselect grouping, and instructor-formed grouping. However, the existing approach of student group formation tend to result in ineffective and unproductive group work as the group members’ skills does not fully complement each other and gives an imbalance impact. Although there are methods in coping this redundancy such as selective appointment method whereas students are grouped based on distinctive skill, personality, and etc. However, this traditional method consumes time and energy as it requires manual effort.